Restructuring surgical training after COVID-19 pandemic: A nationwide survey on the Italian scenario on behalf of the Italian polyspecialistic young surgeons society (SPIGC) - Gallo, Gaetano; Guaitoli, Eleonora; Barra, Fabio; Picciariello, Arcangelo; Pasculli, Alessandro; Coppola, Alessandro; Pertile, Davide; Meniconi, Roberto Luca, SPIGC Surgical Training Working Group; Berton, Federico; Conti, Luigi; Formisano, Giampaolo; et al. (Frontiers in Surgery, 2023)
Introduction The COVID-19 pandemic has led to the disruption of surgical training. Lack of communication, guidelines for managing clinical activity as well as concerns for safety in the workplace appeared to be relevant issues. This study aims to investigate how surgical training has been reorganized in Italy, almost two years after the outbreak of COVID-19 pandemic. Materials and methods A 16-item-electronic anonymous questionnaire was designed through SurveyMonkey© web application. This survey was composed of different sections concerning demographic characteristics and impacts of the second COVID-19 pandemic wave on surgical and research/didactic activities. Changes applied in the training programme and activities carried out were also investigated. Results Four hundred and thirty responses were collected, and 399 were considered eligible to be included in the study analysis. Three hundred and thirty-five respondents continued working in Surgical Units, with a significant reduction (less than one surgical session per week) of surgical sessions in 49.6 % of them. With concern to didactic and research activities, 140 residents maintained their usual activity, while 116 reported a reduction. A sub-group analysis on resident moved to COVID-19 departments showed a reduction of research activities in 35% of them. During the period considered in this survey, the surgical training program was not substantially modified for most of participants (74.6%). Conclusion Our survey demonstrated that surgical residency programs haven’t improved 2 years after the beginning of the pandemic. Further improvements are needed to guarantee completeness of surgical training, even in emergency conditions.